PENGEMBANGAN KUALITAS PRODUK SERAGAM SEKOLAH DENGAN METODE SIX SIGMA DI TPKU PP.TEBUIRENG - Sumarsono; Nur Muflihah; Sulung Rahmawan. W.G; Andhika Mayasari; Minto; Fatma Ayu Nuning F.A (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
TPKU PP.Tebuireng's business is engaged in school uniforms. The results of previous research, it was found that there were seven Critical to Quality (CTQ). The seven CTQs are button attachment, accessories installation, untidy stitching, loose overlock, uniform stain, slanted pocket, and sloping belt. Based on these findings, the objective of the activity is transforming knowledge to develop the quality of school uniform using the six sigma method. The six sigma method is improving quality, aiming 3-4 defects per million products or services. The results of the service activities have been delivery of material and the application of the six sigma method. The six sigma method stages include define, measure, analyze, improve, control. The results of the define application by check sheet, identified seven CTQs. The application of measure is 2.95 sigma level, is equivalent to 74,830 defective in a million productions. The analyze application with pareto and causal diagram shows two types of CTQ. That have dominant causes of defects, namely untidy seams and uniform stains. The implementation of improve is based on the analyze stage results. Implementation of control by means of documentation, disseminate all relevant sections. As a step to improve the performance of the next process.